Geographical distribution modelling of the bronze bug: a worldwide invasion - Montemayor Borsinger, Sara Itzel (2014)
1 The present study investigated the environmental variables that define a suitableclimate for the bronze bug,Thaumastocoris peregrinusCarpintero & Dellapé, usingpresence-only data, with the aim of identifying areas that have a suitable climate(and thus high probability) for future colonization and generating a spatially explicitpredictive map of environmental suitability. An occurrence database (293 records) wascompiled mainly from the literature.2 The environmental data were obtained from the WorldClim 1.3 dataset, and themodels were performed using maxent, version 3.3.3k. Model performance wasevaluated through cross-validation. We used the null models approach to test ourmodels. For model calibration, two datasets were defined (a non conservative datasetand a conservative one) by comparing the bioclimatic variables between native andintroduced range using boxplots.3 According to both models, the range forT. peregrinuswill continue to expand. InSouth America and Africa, the distribution of the bronze bug may expand mainly tothe north-east and central areas. Special attention should be given to the regions ofsouthern U.S.A., Central America, and southern China and nearby countries, whereconditions are highly suitable but the bronze bug has not yet been recorded and couldonly arrive by human means.4 BecauseEucalyptusspecies, many of which are highly susceptible to infestation by thebronze bug, are increasingly being planted around the world, and because the bronzebug has spread so rapidly over the past 8 years, the bronze bug may be expected toappear in many areas where it has not yet been recorded.